2023
DOI: 10.1002/brb3.3118
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin mitigates type 1 diabetes‐aggravated cerebral ischemia‐reperfusion injury through anti‐inflammatory and anti‐apoptotic effects

Abstract: IntroductionCerebral ischemia and diabetes mellitus (DM) are common diseases that often coexist and interact with each other. DM doubles the risk of ischemic stroke, and cerebral ischemia causes stress‐induced hyperglycemia. Most experimental stroke studies used healthy animals. Melatonin is neuroprotective against cerebral ischemia–reperfusion injury (CIRI) in non‐DM, normoglycemic animals through anti‐oxidant effect, anti‐inflammation, and anti‐apoptosis. Previous studies have also reported a negative correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 85 publications
0
0
0
Order By: Relevance
“…In addition, MLT activates Wnt/β-catenin and TGF-β1-Smad2/3 signaling pathways to alleviate oxidative stress, which inhibits TLR4 or NF-κB and TGF-β1/Smad3 signaling pathways to improve renal inflammation and fibrosis ( 17 – 19 ). It has also been reported that MLT serves an essential role in anti-inflammatory processes, such as rheumatoid arthritis ( 20 , 21 ). Yu et al ( 22 ) and Zhang et al ( 23 ) previously reported that MLT can augment mitochondrial function via modulating AMPK activity and autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MLT activates Wnt/β-catenin and TGF-β1-Smad2/3 signaling pathways to alleviate oxidative stress, which inhibits TLR4 or NF-κB and TGF-β1/Smad3 signaling pathways to improve renal inflammation and fibrosis ( 17 – 19 ). It has also been reported that MLT serves an essential role in anti-inflammatory processes, such as rheumatoid arthritis ( 20 , 21 ). Yu et al ( 22 ) and Zhang et al ( 23 ) previously reported that MLT can augment mitochondrial function via modulating AMPK activity and autophagy.…”
Section: Introductionmentioning
confidence: 99%